Renal cell carcinoma: Review of etiology, pathophysiology and risk factors - Petejova, Nadezda; Martinek, Arnost (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
BACKGROUND AND AIMS: The global incidence of renal cell cancer is increasing annually and the causes are multifactorial. Early diagnosis and successful urological procedures with partial or total nephrectomy can be life-saving. However, only up to 10% of RCC patients present with characteristic clinical symptoms. Over 60% are detected incidentally in routine ultrasound examination. The question of screening and preventive measures greatly depends on the cause of the tumor development. For the latter reason, this review focuses on etiology, pathophysiology and risk factors for renal neoplasm. METHODS: A literature search using the databases Medscape, Pubmed, UpToDate and EBSCO from 1945 to 2015. RESULTS AND CONCLUSIONS: Genetic predisposition/hereditary disorders, obesity, smoking, various nephrotoxic industrial chemicals, drugs and natural/manmade radioactivity all contribute and enviromental risks are a serious concern in terms of prevention and the need to screen populations at risk. Apropos treatment, current oncological research is directed to blocking cancer cell division and inhibiting angiogenesis based on a knowledge of molecular pathways.
Keywords: nádory ledvin; Humans; hereditary syndromes; radioactivity; Carcinogenesis; rizikové faktory; lidé; sloučeniny uranu; renal cell carcinoma; Neoplasm Metastasis; metastázy nádorů; staging nádorů; Uranium Compounds; karcinogeneze; nephrectomy; Genetic Predisposition to Disease; genetická predispozice k nemoci; radiační expozice; renal carcinogenesis; Radiation Exposure; karcinom z renálních buněk; uranium toxicity; Carcinoma, Renal Cell; Neoplasm Staging; Kidney Neoplasms; Risk Factors